Analysis Of Literature Review On Spiritual Concepts According To The Perspectives Of The Al-Quran, Hadith And Islamic Scholars - et. al., Azlisham Abdul Aziz, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper aims to explain the concept of spirituality from an argumentative perspective from the al-Qur'an, hadith and Islamic scholars. The term spiritual refers to the intangible aspect of one's being, from Western epistemology, which causes their views to be contrary to Islam, resulting in misconceptions in the application of the concept of spirituality. Meanwhile, religion, according to the Islamic argument, grows in the spiritual dimension. From a Western perspective, however, it is the polar opposite. On the Qur'anic side, the meaning of spirit is used with different words in the al-Qur'an, the most common of which is the word al-qalb, which is mentioned in various verses. Furthermore, al-qalb has several meanings, including al-aql, al-roh, al-ra'y, al-fu'ad, al-sadr, al-nafs al-lubb. Similarly, taqwa, the feeling of absolute love for Allah SWT and the Messenger of Allah SWT, self-confidence, and patience, is mentioned in a spiritually related hadith. According to Islamic scholars, the spiritual dimension of a Muslim's life includes monotheism, worship, and morality.